Pelaksanaan Putusan Hakim Yang Telah Berkekuatan Hukum Tetap Terhadap Uang Pengganti Dalam Tindak Pidana Korupsi Putusan Nomor 02/Pid.Sus-TPK/2017/PN DPS - I Kadek Warga Pernada; I Made Sepud; Diah Gayatri Sudibya (Jurnal Analogi Hukum, 2019)
Corruption is an act that violates the law in terms of detrimental state finances, regional finances, financial institutions/ agencies obtained from official government assistance. The effort to restore lost state finances is by providing additional penalties such as payment of substitute money. The problems of this study include: 1. What is the Qualification of the Criminal Arrangement for Additional Substitution by the Public Prosecutor in Corruption Crime (Decision Number 02 / Pid.Sus-TPK / 2017 / PN DPS)? and 2. What are the obstacles to the implementation of a judge's decision by the prosecutor as the executor of substitute money as an additional criminal act of corruption (Decision Number 02 / Pid.Sus-TPK / 2017 / PN DPS) ?. The research method used is Empirical Research. The results of the study can be concluded that criminal acts of corruption are systematic and organized crimes, which are usually carried out by people who are important in a society. Efforts to return assets resulting from corruption from perpetrators of corruption, namely by providing article 18 of Law No. 31 of 1999 as amended by law No. 20 of 2001 concerning the eradication of criminal acts of corruption in the case of criminal additions to substitute money. Constraints in implementing the judge's decision are: Recognition of convoluted convicts on corrupt property, the amount of proceeds from corruption that is difficult to find. Efforts are made, namely: carrying out assets tracking actions on property owned, confiscating and auctioning off the assets of the convicted person and depositing the results of the auction to the State Treasury.